2019
DOI: 10.1177/1468087419857597
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of diesel engine cylinder deactivation performance during low-load transient operations

Abstract: Fuel-efficient aftertreatment thermal management in modern diesel engines is a difficult challenge, especially during low-load operation. This study explores the performance of cylinder deactivation in a diesel engine during low-load operation following highway cruise through experimental evaluation of two drive cycles, specifically extended idle and repeated heavy heavy-duty diesel truck creep cycles. Cylinder deactivation operations are shown to maintain comparable aftertreatment thermal management performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
(29 reference statements)
0
22
0
Order By: Relevance
“…Many previous studies have shown that CDA is an effective method to slow the cooling of after-treatment components during lowloads through reduced exhaust flow and increased exhaust temperatures. [30][31][32] The exhaust temperature and flow rate are effective thermal management indicators to understand the after-treatment thermal management characteristics of an operating point. 29 Allen et al 31 explored the performance of cylinder deactivation in a diesel engine during the low-load operation following highway cruise through experimental evaluation of two drive cycles, specifically extended idle and repeated heavy heavy-duty diesel truck creep cycles.…”
Section: Cylinder Deactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have shown that CDA is an effective method to slow the cooling of after-treatment components during lowloads through reduced exhaust flow and increased exhaust temperatures. [30][31][32] The exhaust temperature and flow rate are effective thermal management indicators to understand the after-treatment thermal management characteristics of an operating point. 29 Allen et al 31 explored the performance of cylinder deactivation in a diesel engine during the low-load operation following highway cruise through experimental evaluation of two drive cycles, specifically extended idle and repeated heavy heavy-duty diesel truck creep cycles.…”
Section: Cylinder Deactivationmentioning
confidence: 99%
“…[30][31][32] The exhaust temperature and flow rate are effective thermal management indicators to understand the after-treatment thermal management characteristics of an operating point. 29 Allen et al 31 explored the performance of cylinder deactivation in a diesel engine during the low-load operation following highway cruise through experimental evaluation of two drive cycles, specifically extended idle and repeated heavy heavy-duty diesel truck creep cycles. The results indicated that CDA can reduce the fuel up to 40% during extended idle operation and maintain the same after-treatment thermal management performance.…”
Section: Cylinder Deactivationmentioning
confidence: 99%
“…Retarding or advancing nominal IVC timing decreases air intake and increases engineout temperatures. Another air-reducing technique is to use cylinder deactivation (CDA) [19][20][21][22]. In this method, some of the cylinders on the system are inactivated through switching off both valves and fuel injection.…”
Section: Introductionmentioning
confidence: 99%
“…18 Maintaining elevated aftertreatment temperatures is a challenge, especially at low-load diesel engine operation, as the engine-outlet temperatures are too low at these operating conditions. 911 Elevated temperatures at low-load operating conditions are typically achieved by making the engine operation inefficient, for example, by increasing the back-pressure to increase the pumping losses, delaying fuel injections to make the combustion process thermodynamically inefficient and intake throttling to reduce airflow.…”
Section: Introductionmentioning
confidence: 99%